Nigeria in Search of Unifying Factor, Introduction of Festival of Interest as a Panacea - Rasheed Adeniyi Tiamiyu (Journal of Governance and Public Policy, 2020)
It has been observed that Nigeria’s National flag, coat of arms, anthem, Pledge and motto: Peace and Unity, Strength and Progress has not ignited much love of her citizen for the unity of Nigeria and cohesion of nationalism required to ward off antics of some developed countries instigating discordance in the developing countries to benefit their business interest. Nigeria has the largest population of any African country and as such, anything which may threaten its unity must be a concern to any discern mind of any black race. To be able to come up with what could serve as catalyst of unity, this paper considered the struggle for independence which made Nigerian to see themselves not as Hausas, Igbos, or Yorubas, but as Nigerians in a common struggle against their colonial rulers and such unity the country had during the election that would have made Chief M.K.O. Abiola the president of Nigeria, but truncated. It was discovered that love for the country and the person was the key in the observed unity. Therefore, this paper looked at what could be used as stimulant of love for the unity of Nigeria since, the three main environmental regions of coastal wetland in the East, tropical forests in the West and savanna in the North along with National Youth Service Corps and Unity Schools established to be factors of unity have also failed to stem up nationalism in Nigerians.